2012
DOI: 10.1186/1471-2458-12-283
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of heart attack and stroke symptomology: a cross-sectional comparison of rural and non-rural US adults

Abstract: BackgroundUnderstanding the signs and symptoms of heart attacks and strokes are important not only in saving lives, but also in preserving quality of life. Findings from recent research have yielded that the prevalence of cardiovascular disease risk factors are higher in rural populations, suggesting that adults living in rural locales may be at higher risk for heart attack and/or stroke. Knowledge of heart attack and stroke symptomology as well as calling 911 for a suspected heart attack or stroke are essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 23 publications
6
40
1
1
Order By: Relevance
“…Our findings showed no association between personal income and the knowledge and awareness. In a study in the US, subjects living in rural areas are more likely to have lower knowledge on heart attack and stroke if they are not graduate from high school and are economically poor [26]. In Jordan, Mukattash et al (2012) showed significant association between the socioeconomics and the knowledge on CVDs.…”
Section: Discussionmentioning
confidence: 96%
“…Our findings showed no association between personal income and the knowledge and awareness. In a study in the US, subjects living in rural areas are more likely to have lower knowledge on heart attack and stroke if they are not graduate from high school and are economically poor [26]. In Jordan, Mukattash et al (2012) showed significant association between the socioeconomics and the knowledge on CVDs.…”
Section: Discussionmentioning
confidence: 96%
“…This study used participant responses primarily from the demographics, HRQOL, chronic health, and physical activity cores. A total of N=65,492 adults 20+ years of age, who answered all relevant survey questions, and resided in a rural U.S. county were included [12].…”
Section: Participants and Designmentioning
confidence: 99%
“…Knowledge of heart attack and stroke symptomology has been the focus of much research based on the assumption that accurate identification of an event is critical to reducing time to treatment [7]. It is well established that early treatment for both heart attack and stroke is critical in lowering the risk for poor outcomes [8] and preserving quality of life [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been conducted in order to ascertain specific populations of US adults with knowledge deficits in the areas of first responder action as well as heart attack and stroke symptomology [7,[11][12][13][14][15]. It is believed that by identifying these populations of adults, better public health campaigns can be aimed at enhancing knowledge [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%